The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1139/f00-108
|View full text |Cite
|
Sign up to set email alerts
|

Element export in runoff from eastern Canadian Boreal Shield drainage basins following forest harvesting and wildfires

Abstract: Element export rates from the drainage area of nine harvested, nine burnt, and 16 reference Boreal Shield lake basins in Haute-Mauricie, Québec, were estimated for the 3 years following harvesting or fires. Export rates from the drainage area of the basins were evaluated using lake sampling surveys, estimated hydrological budgets, and estimated nutrient retention during lake transit. Increases in K + , total N, and total P export rates were similar between harvested and burnt drainage areas. However, harvested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 24 publications
(23 reference statements)
3
68
1
Order By: Relevance
“…Possibly clear-cutting increase stream water nutrient concentrations less in northern than in southern Fennoscandia due to slower mineralization rates and lower deposition fluxes (Akselsson et al 2004;Kortelainen et al 2006;Futter et al 2010;Palviainen et al 2014), and in the northern catchments the observed rise in nutrient loading is largely due to the increased runoff (Ahtiainen and Huttunen 1999;Palviainen et al 2014). The increase in total N, NO 3 -N, NH 4 -N and PO 4 -P concentrations after clear-cutting is in accordance with the results from other boreal catchments (Grip 1982;Rosén et al 1996;Lamontagne et al 2000;Kreutzweiser et al 2008). The increases in the concentrations of N fractions in stream water could result from higher deposition loads due to the lack of N retention by tree canopy (Piirainen et al 2002), reduced nutrient uptake by trees and understory vegetation (Palviainen et al 2007), and increased nitrification in litter layer and soil (Paavolainen and Smolander 1998).…”
Section: Specific Concentrationssupporting
confidence: 85%
See 2 more Smart Citations
“…Possibly clear-cutting increase stream water nutrient concentrations less in northern than in southern Fennoscandia due to slower mineralization rates and lower deposition fluxes (Akselsson et al 2004;Kortelainen et al 2006;Futter et al 2010;Palviainen et al 2014), and in the northern catchments the observed rise in nutrient loading is largely due to the increased runoff (Ahtiainen and Huttunen 1999;Palviainen et al 2014). The increase in total N, NO 3 -N, NH 4 -N and PO 4 -P concentrations after clear-cutting is in accordance with the results from other boreal catchments (Grip 1982;Rosén et al 1996;Lamontagne et al 2000;Kreutzweiser et al 2008). The increases in the concentrations of N fractions in stream water could result from higher deposition loads due to the lack of N retention by tree canopy (Piirainen et al 2002), reduced nutrient uptake by trees and understory vegetation (Palviainen et al 2007), and increased nitrification in litter layer and soil (Paavolainen and Smolander 1998).…”
Section: Specific Concentrationssupporting
confidence: 85%
“…In addition, increased soil temperatures following clear-cutting accelerate mineralization and nitrification in the soil (Paavolainen and Smolander 1998;Smolander et al 2001) and nutrients are released from decomposing logging residues (Palviainen et al 2004). Clear-cutting may also increase total or dissolved organic carbon (TOC, DOC) export (Lamontagne et al 2000;Schelker et al 2012Schelker et al , 2014, which have implications for catchment carbon budgets (Schelker et al 2012), the structure of aquatic food webs (Jansson et al 2000), the acid-base chemistry of surface waters (Buffam et al 2008), and the mobility, toxicity, and bioavailability of trace metals and organic pollutants (Porvari et al 2003;Bergknut et al 2011). The impacts on water quality are long-term and they are generally at its greatest during the first years after clear-cutting (Rosén et al 1996;Ahtiainen and Huttunen 1999;Palviainen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether there will be an increased export of N after harvesting to aquatic systems depends on the coincident occurrence of increased production and/or decreased uptake by plants and microorganisms within the terrestrial ecosystem and the ability to transfer these nutrients to adjacent receiving waters. The minimal surface water impacts of harvesting reported for the Canadian boreal forest region (Nicolson et al, 1982;Carignan et al, 2000;Lamontagne et al, 2000;Steedman 2000;Prepas et al, 2001), even in studies where no shoreline buffer zones had been established, may be partly explained by the limited potential of upland boreal forest soils to mineralize organic-N to inorganic forms. In general, unharvested boreal forest organic and mineral soils have been shown to have low net inorganic-N production, particularly NO À 3 -N. This has been shown in Quebec (Brais et al, 1995;Smith et al, 2000) and Michigan (Stottlemyer and Toczydlowski, 1999) on the boreal shield and in Saskatchewan on the boreal plain (Walley et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Increased carbon (C), nitrogen (N), phosphorus (P), and suspended solids (SS) export to watercourses have often been observed after the clear-cutting of boreal forests (Grip 1982;Rosén et al 1996;Ahtiainen and Huttunen 1999;Lamontagne et al 2000;Laudon et al 2009;Schelker et al 2012). This is due to increased runoff, elevated concentrations or both.…”
Section: Introductionmentioning
confidence: 99%